Superconductors without Symmetry Breaking - Maria Cristina Diamantini (Condensed Matter, 2024)
We review the main features of type-III superconductivity. This is a new type of superconductivity that exists in both 2 and 3 spatial dimensions. The main characteristics are emergent granularity and the superconducting gap being opened by a topological mechanism, with no Higgs field involved. Superconductivity is destroyed by the proliferation of vortices and not by the breaking of Cooper pairs, which survive above the critical temperature. The hallmark of this superconductivity mechanism, in 3 spatial dimensions (3D), is the Vogel–Fulcher–Taman scaling of the resistance with temperature.